2001
DOI: 10.1046/j.1365-294x.2001.01325.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of fine roots of trees from the Alps: reliable and fast DNA extraction and PCR–RFLP analyses of plastid DNA

Abstract: Fine roots of trees are intensively used as indicators to assess soil alterations, e.g. those owing to atmospheric inputs of acidifying substances, but their identification to species with morphological criteria is difficult. In this study, we established molecular techniques in order to identify fine roots of the 30 most common tree species of the Alps. We developed a protocol for efficient isolation of DNA from fine roots with extraction of DNA in the presence of polyvinylpyrrolidone (PVP) and polyvinylpolyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 36 publications
0
94
0
Order By: Relevance
“…It is known that polyvinylpyrrolidone (PVP) adsorbs the polyphenol and β-mercaptoethanol shows an antioxidative effect (e.g. Porebski et al 1997;Dempster et al 1999;Khanuja et al 1999;Brunner et al 2001;Biss et al 2003;Bharmauria et al 2010;Kejani et al 2010). In the present study, the extraction solution with the modified CTAB method contained PVP and β-mercaptoethanol, and it is suggested that this DNA extraction technique is effective both to remove the polyphenol and to curb the oxidization of polyphenol.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that polyvinylpyrrolidone (PVP) adsorbs the polyphenol and β-mercaptoethanol shows an antioxidative effect (e.g. Porebski et al 1997;Dempster et al 1999;Khanuja et al 1999;Brunner et al 2001;Biss et al 2003;Bharmauria et al 2010;Kejani et al 2010). In the present study, the extraction solution with the modified CTAB method contained PVP and β-mercaptoethanol, and it is suggested that this DNA extraction technique is effective both to remove the polyphenol and to curb the oxidization of polyphenol.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al (2011), therefore, used trnH-psbA to discriminate between 33 species from 117 root fragments. However, in recent root studies, an alternative, and often less species specific, barcode (trnL) is more frequently used (Brunner et al 2001;Ridgway et al 2003;Frank et al 2010;Dumbrell et al 2010;Taggart et al 2011). This variety in the usage of different barcode primers reflects that primer choices will always need to be adjusted to the molecular differentiation found across species within a particular community or experimental system.…”
Section: Developing Methodological Tools For Root Ecologymentioning
confidence: 99%
“…The species of root branches <2 mm in diameter were identified with molecular genetic methods using the procedure described by Brunner et al (2001). We analyzed 2-5 root branches from the surface layer of each of the six pit samples at Bartlett.…”
Section: Molecular Confirmation Of Root Identificationmentioning
confidence: 99%
“…Root samples were ground in an amalgamator (Darby Dental, Akron, Ohio). DNA was extracted from approximately 30 mg of each sample using a standard alkaline lysis or chloroform extraction procedure modified with addition of polyvinylpolypyrrolidone, polyvinylpyrrolidone, betamercaptoethanol, and spermidine, to improve extraction efficiency and inhibitor removal (Brunner et al 2001). The plastid trnL intron was amplified using primers c and d (Taberlet et al 1991) and PCR products were digested with taqI.…”
Section: Molecular Confirmation Of Root Identificationmentioning
confidence: 99%